Automatic household waste separation system based on resistance value and moisture content - Ahamad, Nurul Nazihah; Mohamad, Sarah Yasmin; Midi, Nur Shahida; Yusoff, Siti Hajar; Rahman, Faridah Abd (Institute of Advanced Engineering and Science, 2019)
In the new era of globalization, waste disposal has turned into an immense concern among the nation. Nowadays, almost every part of the world is confronting a huge issue of improper disposal, segregation and recycling solid waste. Due to rapid growth in economy, industrialization and urbanization, there is also a rapid increase of capacity and volume of solid waste. As a result, improper management of solid waste lead to disturbance to the environment and human health. In this paper, a fully automated waste separation system to discriminate residual and recyclable waste is proposed. The system is designed to focus on household waste, since household waste ranks the highest volume of waste among others. It is designed to separate household waste into recyclable and residual waste according to the materials’ state, which is dry and wet, by employing a moisture sensor to the waste separation system.